THE ATLAS EXPERIMENT ON-LINE MONITORING AND FILTERING AS AN EXAMPLE OF REAL-TIME APPLICATION - Korcyl, K.; Szymocha, T.; Funika, W.; Kitowski, J.; Słota, R.; Balos, K.; Dutka, L.; Guzy, K.; Kryza, T.; Pieczykolan, J. (Computer Science, 2013)
The ATLAS detector, recording LHC particles’ interactions, produces events with rate of40 MHz and size of 1.6 MB. The processes with new and interesting physics phenomena arevery rare, thus an efficient on-line filtering system (trigger) is necessary. The asynchronouspart of that system relays on few thousands of computing nodes running the filtering software.Applying refined filtering criteria results in increase of processing times what may lead tolack of processing resources installed on CERN site. We propose extension to this part ofthe system based on submission of the real-time filtering tasks into the Grid.